Universal one-pot, one-step synthesis of core-shell nanocomposites with self-assembled tannic acid shell and their antibacterial and catalytic activities - Fang, Yan (2019)
Facile synthesis of metal@polymer nanocomposites were achieved using self‐assembled tannic acid (TA) shells without crosslinkers. The TA shell was assembled under mildly alkaline conditions in reaction time of 20 min under constant vortexing. Universal synthesis method was demonstrated by the synthesis of Ag@TA and Au@TA nanocomposites. We propose that the shell formation is due to TA undergoing oxidative self‐polymerization to poly(tannic acid) or a supramolecular aggregate of oxidized TA held together by charge transfer, hydrogen bond, and π–π interactions, similar to dopamine polymerization. Gibbs free energy calculations suggest that polymerization is energetically favorable. Synthesized Ag@TA exhibited antibacterial functionality with Escherichia coli minimum inhibitory concentration of 100 µg mL−1 up to 48 h. The population of E. coli was also reduced by 99% within 5 h when incubated with 100 µg mL−1 of Ag@TA nanocomposite. Au@TA also functions as a reduction catalyst. It reduces 4‐nitrophenol to 4‐aminophenol in the presence of NaBH4 with a rate constant of k = 0.63 min−1 μmol−1. For comparison, using Au nanoparticles yields a rate constant of 0.14 min−1 μmol−1. The ease of synthesis renders the nanocomposites superior to others, with potential for large‐scale application.